METHOD AND DEVICE FOR OPERATING AN INERTIAL SENSOR UNIT FOR A VEHICLE - EWERT MARLON RAMON (2020)
The invention relates to a method (100) for operating an inertial sensor unit for a vehicle, comprising the following steps: a, detecting (101) inertial sensor data, driving direction data and/or steering angle data and/or wheel rotational speeds during the journey of the vehicle; b, determining (102) a correction matrix for the inertial sensor data subject to the detected driving direction data and/or steering angle data; c, determining (103) a transformation matrix for the inertial sensor data for a target coordinate system subject to the driving direction data and/or steering angle data; d,transforming (104) the inertial sensor data by means of the correction matrix and/or transformation matrix; e, outputting (105) the transformed inertial sensor data. 本发明涉及一种用于运行用于车辆的惯性传感器单元的方法(100)，该方法具有步骤：a.在车辆的行驶期间获取(101)惯性传感器数据、行驶方向数据和/或转向角度数据和/或车轮转速；b.根据所获取的行驶方向数据和/或转向角度数据求取(102)用于惯性传感器数据的校正矩阵；c.根据行驶方向数据和/或转向角度数据为目标坐标系求取(103)用于惯性传感器数据的变换矩阵；d.借助于校正矩阵和/或变换矩阵变换(104)惯性传感器数据；e.输出(105)变换后的惯性传感器数据。